2001
DOI: 10.1152/ajprenal.2001.281.6.f1117
|View full text |Cite
|
Sign up to set email alerts
|

Role of NHE isoforms in mediating bicarbonate reabsorption along the nephron

Abstract: This study assessed the functional role of Na(+)/H(+) exchanger (NHE) isoforms NHE3 and NHE2 in the proximal tubule, loop of Henle, and distal convoluted tubule of the rat kidney by comparing sensitivity of transport to inhibition by Hoe-694 (an agent known to inhibit NHE2 but not NHE3) and S-3226 (an agent with much higher affinity for NHE3 than NHE2). Rates of transport of fluid (J(v)) and HCO(3)(-) (J(HCO3)) were studied by in situ microperfusion. In the proximal tubule, addition of ethylisopropylamiloride … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 38 publications
3
68
0
2
Order By: Relevance
“…The H + -ATPase is selectively localized to luminal membranes and submembranous vesicles. It has also been demonstrated that the luminal membranes of the TALs possess NHE3 and another Na + /H + exchanger NHE2 in rat kidneys (Wang et al 2001;Capasso et al 2002). In our experimental protocol, we examined the involvement of these Na + /H + exchangers in the luminal membranes of the mTALs by either inhibiting ambient Na + with a high dose of amiloride or eliminating ambient Na + .…”
Section: Relation To H + -Atpase and Na + /H + Exchangers In The Lumimentioning
confidence: 97%
“…The H + -ATPase is selectively localized to luminal membranes and submembranous vesicles. It has also been demonstrated that the luminal membranes of the TALs possess NHE3 and another Na + /H + exchanger NHE2 in rat kidneys (Wang et al 2001;Capasso et al 2002). In our experimental protocol, we examined the involvement of these Na + /H + exchangers in the luminal membranes of the mTALs by either inhibiting ambient Na + with a high dose of amiloride or eliminating ambient Na + .…”
Section: Relation To H + -Atpase and Na + /H + Exchangers In The Lumimentioning
confidence: 97%
“…As for the proximal tubule, proton and bicarbonate transport in the thick ascending limb of Henle's loop are mediated by the vacuolar H ϩ -ATPase, along with other transporters including the Na ϩ /H ϩ exchanger NHE-3 (96,554). Both the electroneutral NBC(N)1 (538) and electrogenic NBC4 (577) are expressed in the thick ascending limb (TAL).…”
Section: B Loop Of Henlementioning
confidence: 99%
“…The main Na ϩ /H ϩ exchanger isoform is NHE-3, but NHE-2 may also play a role (98,554). The reabsorbed HCO 3 Ϫ is excreted into blood possi-bly through a K ϩ -dependent HCO 3 Ϫ pathway (56), the molecular identity of which is not resolved.…”
Section: B Loop Of Henle and Talmentioning
confidence: 99%
“…In mammals, NHE2 is primarily found in skeletal muscle, kidney, and the gastrointestinal tract, whereas NHE3 is mainly in the renal tubule, intestine, and stomach (39,70). NHE3 is the predominant apical exchanger in the renal proximal tubule and is upregulated during metabolic acidosis (43,68), whereas NHE2 may be the predominant isoform in the distal convoluted tubule (63) and apical membranes of colonic crypts (30). Phylogenetic analysis of the NHE family indicates that NHE1, NHE2, and NHE4 are closely related (all belonging to the resident plasma membrane NHE clade; see Ref.…”
mentioning
confidence: 99%